2021
DOI: 10.1039/d1cp03161a
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of glyphosate zwitterions and conformational/tautomerism mechanism in aqueous solution: insights from ab initio and density functional theory-continuum model calculations

Abstract: Theoretical investigation of the conformational interconversion equilibria and the ZW ⇋ NE tautomerization process of glyphosate in an aqueous solution using IEFPCM and SMD continuum solvation models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 62 publications
2
12
1
1
Order By: Relevance
“…However, this estimate had been based on the energy comparison of single structures and on the use of implicit solvation. Conversely, several literature studies have shown that the computational estimate of the stability of the zwitterion vs nonzwitterion form of either amino acids or peptides was rather challenging and ideally required the employment of high levels of theory, multiconformational representations of the investigated molecules, and explicit solvation. …”
Section: Resultsmentioning
confidence: 99%
“…However, this estimate had been based on the energy comparison of single structures and on the use of implicit solvation. Conversely, several literature studies have shown that the computational estimate of the stability of the zwitterion vs nonzwitterion form of either amino acids or peptides was rather challenging and ideally required the employment of high levels of theory, multiconformational representations of the investigated molecules, and explicit solvation. …”
Section: Resultsmentioning
confidence: 99%
“…FSC can interact with 3D‐POWER via π–π stacking, whereas GLY interacts with the surface chemistry of 3D‐POWER by means of the phosphonate group in P‐O − , P═O − and P‐C‐N‐H bonds, which is stabilized by hydrogen interactions. [ 19 ] However, given the molecular flexibility of GLY (due to its single bonds, see Figure S14 , Supporting Information), a concentration‐dependent SERS fingerprint was observed for this analyte. Hence, the surface coverage of GLY onto 3D‐POWER may modulate the orientation of GLY yielding such a concentration‐dependent spectroscopic behavior, [ 20 ] where the lowest concentrations of GLY allowed for the best observations of a highly detailed Raman signature of GLY by means of 3D‐POWER, see Figures S14 and S15 (Supporting Information), particularly, displaying clearly defined vibrational bands associated to the phosphonate group, see Table S11 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…34,35 The integral equation formalism polarizable continuum model (IEFPCM) was applied in all the DFT calculations to approximate the solid environment, with the dielectric constant set to 4. 36–41…”
Section: Methodsmentioning
confidence: 99%